Feeding Protocol Modulates the Digestive Process in Senegalese Sole (Solea senegalensis) Juveniles - Gilannejad, Neda; Moyano, Francisco J.; Martínez-Rodríguez, Gonzalo; Yúfera, Manuel (Frontiers in Marine Science, 2021)
Understanding the daily digestive function could lead to more efficient feeding practices in the farmed fish species. In this work, the effect of several daily feeding protocols was assessed on the daily expression of the genes related to the circadian system (arntl1, clock, per1 and cry1), appetite (cck), nutrients hydrolysis (try1, ctrb1, pga, atp4a, cel, and amy2a), peptides transport (slc15a1), pH, and activity of key digestive (trypsin, chymotrypsin, amylase, 4C- and 7C-like lipases) and absorptive (alkaline phosphatase) enzymes in the gastrointestinal tract (GIT) of Senegalese sole (Solea senegalensis) juveniles. Some of the tested feeding protocols demonstrated a significant influence on the entrainment of the peripheral oscillator. The synchrony of slc15a1 and some digestive proenzymes with per1 in some of the experimental treatments could underline the role of clock genes in the regulation of these biological functions. Unlike gene expression of the digestive proenzymes wherein feeding protocol occasionally affected the temporal organization, the influence of this factor was determinant on the daily average production and/or circadian pattern of their activities. Daily pH was maintained at approximately neutral levels in all the GIT segments and no pepsin activity was detected. Fish fed a single diurnal meal showed the lowest activity for all the studied enzymes, except for amylase, suggesting an insufficient utilization of the ingested nutrients. Higher amylase activity in this group, on the other hand, implies the possible activation of alternative compensatory metabolic pathways. Overall, our results pointed to the suitability of higher feeding frequencies, especially during dark hours, for the aquaculture production of this species.